The rise of nativist populism in South Africa: an examination of populist supply and demand from the Economic Freedom Fighters and its support base - Henkeman, Carlynn Tiffany (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.